2017
DOI: 10.1097/sle.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted Tranversus Abdominis Plane (TAP) Block Versus Ultrasonography-guided Transversus Abdominis Plane Block in Postlaparoscopic Cholecystectomy Pain Relief: Randomized Controlled Trial

Abstract: Laparoscopy-assisted TAP block is faster and equally efficacious when compared with USG-guided block and has a definite role in centers where ultrasound is not available in operating rooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…However the surgical technique resulted in a 60 to 80% decrease in performance time. 56,58 In contrast, in one trial investigating minimally invasive colorectal surgery, surgical lateral transversus abdominis plane blocks resulted in similar pain scores but 17.2-mg-lower intravenous morphine consumption at 48 h than their anesthesiologist-performed counterparts. 59 In summary, based on the current knowledge, we suggest foregoing landmark guidance in favor of ultrasound for the performance transversus abdominis plane blocks.…”
Section: Transversus Abdominis Plane Blockmentioning
confidence: 97%
See 1 more Smart Citation
“…However the surgical technique resulted in a 60 to 80% decrease in performance time. 56,58 In contrast, in one trial investigating minimally invasive colorectal surgery, surgical lateral transversus abdominis plane blocks resulted in similar pain scores but 17.2-mg-lower intravenous morphine consumption at 48 h than their anesthesiologist-performed counterparts. 59 In summary, based on the current knowledge, we suggest foregoing landmark guidance in favor of ultrasound for the performance transversus abdominis plane blocks.…”
Section: Transversus Abdominis Plane Blockmentioning
confidence: 97%
“…To date, four randomized controlled trials (Jadad scores of at least 3) have compared surgeon-and anesthesiologist-performed transversus abdominis plane blocks. [56][57][58][59] In three studies investigating subcostal transversus abdominis plane blocks performed for laparoscopic cholecystectomy, 56 and lateral transversus abdominis plane blocks performed for Cesarean delivery 58 or laparoscopic colorectal surgery, 57 surgical and anesthesiologist-driven transversus abdominis plane blocks provided similar postoperative analgesia and breakthrough opioid consumption. However the surgical technique resulted in a 60 to 80% decrease in performance time.…”
Section: Transversus Abdominis Plane Blockmentioning
confidence: 99%
“…Studies have shown that the laparoscopically assisted TAP blocks result in similar pain scores and postoperative opioid consumption 31 32 but shorter block performance time compared with the ultrasound-guided block. 31 In addition, patients receiving a laparoscopically assisted TAP block had statistically significant reduction in pain scores and opioid consumption compared with controls. 30 33 A similar laparoscopically guided technique has been described for rectus sheath block.…”
Section: Introduction Backgroundmentioning
confidence: 93%
“…[8][9][10][11][12] Furthermore, several reports show that laparoscopic-assisted TAP block may be considered equally effective as the standard US-guided TAP block and can be considered the choice in centers where ultrasound is not always available in operating rooms. [11][12][13] More recently, intraoperative laparoscopic-assisted trocar-site bupivacaine infiltration 10,12,14,15 has shown promising results, in terms of post-operative pain relief, in different kinds of miniinvasive surgery. Thus, the aim of this evaluation is to investigate the possible role of laparoscopic-assisted trocar-site ropivacaine infiltration during laparoscopic adrenalectomy (via the lateral transperitoneal approach) in terms of post-operative pain control.…”
Section: Introductionmentioning
confidence: 99%